2014
DOI: 10.3319/tao.2013.10.03.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

Unique Dispersal of the Changjiang-Diluted Water Plume in the East China Sea Revealed from Satellite Monitoring of Colored Dissolved Organic Matter (CDOM)

Abstract: The optical properties of colored dissolved organic matter (CDOM) in the Changjiang (Yangtze River) plume water were investigated during the summer of 2009 and 2010. The absorption coefficient of CDOM at 325 nm (aCDOM) increased inversely with decreasing sea-surface salinity (SSS), implying that aCDOM can be used as a natural tracer of Changjiangdiluted water (CDW). This aCDOM vs. SSS relationship, however, differed between 2009 and 2010. For mapping the CDW plume, the aCDOM was retrieved from an ocean-color s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
(43 reference statements)
2
10
0
Order By: Relevance
“…Several sensors for environmental monitoring have been developed for marine applications (e.g., MODerate resolution Imaging Spectroradiometer, MODIS), but their coarse spatial resolutions, ranging from 250 m to 1200 m, are not suitable for most inland waters bodies [15,18,19]. Recently, the potential for inland water applications has been enhanced by the development of sensors with higher spatial and radiometric resolution [20][21][22][23][24]. The Sentinel-2 multispectral instrument (MSI) is a state-of-art sensor with freely available images at a spatial resolution of 10 m in the visible range that was designed for land applications, but with promising utility for monitoring regional lake water quality [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Several sensors for environmental monitoring have been developed for marine applications (e.g., MODerate resolution Imaging Spectroradiometer, MODIS), but their coarse spatial resolutions, ranging from 250 m to 1200 m, are not suitable for most inland waters bodies [15,18,19]. Recently, the potential for inland water applications has been enhanced by the development of sensors with higher spatial and radiometric resolution [20][21][22][23][24]. The Sentinel-2 multispectral instrument (MSI) is a state-of-art sensor with freely available images at a spatial resolution of 10 m in the visible range that was designed for land applications, but with promising utility for monitoring regional lake water quality [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, southerly wind-driven upwelling, mixing, and sea surface currents shape the eastward dispersion of low SSS (Lie et al, 2003;Xuan et al, 2012) and nutrients (Gao et al, 2015) into patches rather than a continuous, tongue-like protrusion. south of Kyushu Island, Japan, and has been attributed in part to high Changjiang discharge (Sasaki et al, 2014). The annual maximum of the monthly average discharge of the Changjiang in 2010 occurred in July and was about 65,000 m 3 s 21 (Sasaki et al, 2014), much higher than the July climatological monthly peak of 50,000-52,500 m 3 s 21 (e.g., Moon et al, 2012;Siswanto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on satellite ocean color observations, Sasaki et al () have reported a rare dispersion of low‐SSS and high‐gelbstoff water during the summer of 2010 in the ECS. This low‐SSS and high‐gelbstoff water extended in an elongated protrusion from the ECS continental shelf edge northeastward to the area south of Kyushu Island, Japan, and has been attributed in part to high Changjiang discharge (Sasaki et al, ). The annual maximum of the monthly average discharge of the Changjiang in 2010 occurred in July and was about 65,000 m 3 s −1 (Sasaki et al, ), much higher than the July climatological monthly peak of 50,000–52,500 m 3 s −1 (e.g., Moon et al, ; Siswanto et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations